(untitled) (Research, Society and Development, 2024)
Gypsum is widely used in the construction industry, especially as a hydraulic binder. Studies have indicated the use of α-HH gypsum as an alternative material to Portland Cement in oilwell cementing operations, highlighting the reduction in environmental impacts from the reduction of Portland Cement. Calcium Sulphate α-Hemihydrate (CaSO4 . ½ H2O) has been shown to be a promising material to replace Portland Cement in some applications. The hydration of gypsum pastes goes through the process of saturation of the medium with Ca+2 and SO4-2 ions, then the physical phenomenon of crystallization, and finally the phenomenon of hardening, where the crystals formed precipitate producing Dihydrate (CaSO4 . 2H2O). Gypsum pastes harden very quickly, and their pumpability is impaired with thickening times of less than 20 minutes. For applications requiring longer pumpability times, the use of retarding additives is necessary. This research studied the effects of retarding additives in α-HH gypsum paste systems by varying the water-gypsum factor (FAG 0.4; 0.5 and 0.6) using a pressurized consistometer, under conditions of 54 °C and 9500 psi, with the aim of obtaining formulations with admissible thickening times for oil well cementing applications. The results showed that it was possible to develop paste systems with varying thickening times, with intervals of more than 120 minutes. The 0.5 FAG system proved to be more stable at the same retarder concentrations when compared to the 0.4 and 0.6 FAG systems.